1993
DOI: 10.1136/oem.50.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Markers of early renal changes induced by industrial pollutants. II. Application to workers exposed to lead.

Abstract: The present study has been carried out in the framework of a collaborative research project on the development of new markers of nephrotoxicity. A battery of more than 20 potential indicators of renal changes has been applied to 50 workers exposed to lead (Pb) and 50 control subjects. After application of selection criteria 41 exposed and 41 control workers were eventually retained for the final statistical analysis. The average blood Pb concentration of exposed workers was 480 micrograms/l and their mean dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 37 publications
2
34
1
2
Order By: Relevance
“…Cardenas et al (113) used a battery of more than 20 potential indicators of renal function in 50 workers exposed to lead and in 50 control subjects. The most striking effect of lead was interference with renal synthesis of eicosanoids, resulting in lower excretion of 6-keto-PGF l. Increased urinary NAG activity was also found in lead-exposed workers.…”
Section: Lead Nephropathymentioning
confidence: 99%
“…Cardenas et al (113) used a battery of more than 20 potential indicators of renal function in 50 workers exposed to lead and in 50 control subjects. The most striking effect of lead was interference with renal synthesis of eicosanoids, resulting in lower excretion of 6-keto-PGF l. Increased urinary NAG activity was also found in lead-exposed workers.…”
Section: Lead Nephropathymentioning
confidence: 99%
“…Among workers exposed to lead, the excretion of the vasodilator PGI2 was significantly lower than in controls, whereas the excretion of the vasoconstrictor TXB2 was significantly higher. Cadmium exposure among workers was associated with increased excretion of both 6-keto-PGFiu and PGE2 and no change in the excretion of PGF2a or TXB2' These findings may have mechanistic implications for the controversial question of how metal exposure, especially exposure to lead, affects blood pressure (8).…”
Section: Potential New Biomarkersmentioning
confidence: 87%
“…Through the use of biomarkers of damage to various parts of the nephron, a pattern of damage is emerging that is consistently observed now both in U.S. and European studies of men occupationally exposed to cadmium (4)(5)(6)(7)(8)(9)(10) The lowest observed effect is indicated by a significant prevalence of abnormal 6-keto-prostaglandin Fla (6-keto-PGFi,a) and sialic acid levels in urine at an approximate urine cadmium concentration of 2.4 nmol Cd/mmol creatinine (2.4 pg Cd/g creatinine) (10). Proteins such as albumin and transferrin originate in the plasma and are filtered to a limited degree through the glomerulus, and the protein that is filtered is primarily reabsorbed by the tubules.…”
Section: Thresholds Of Effects: Cadmiummentioning
confidence: 99%
See 2 more Smart Citations